2021
DOI: 10.1038/s41598-021-91184-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of beta-adrenergic receptor subtypes in pig uterus contractility with inflammation

Abstract: Uterine inflammation is a very common and serious condition in domestic animals. To development and progression of this pathology often lead disturbances in myometrial contractility. Participation of β1-, β2- and β3-adrenergic receptors (ARs) in noradrenaline (NA)-influenced contractility of the pig inflamed uterus was studied. The gilts of SAL- and E.coli-treated groups were administered saline or E.coli suspension into the uterine horns, respectively. Laparotomy was only done in the CON group. Compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…For example, a difference in NO 69 and PGE 2 70 amounts between the particular layers in both healthy and inflamed pig uteri was demonstrated. Earlier it was reported that NA, ACh, NPY, VIP, GAL and PGE 2 have lowering action on the amplitude in pig inflamed uterus 31,32,38,39,41,43,44 . Thus, it is possible, that CGRP by decreasing the value of this parameter (present study) is another substance which contributes to the accumulation of inflammatory exudate inside the uterine lumen.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, a difference in NO 69 and PGE 2 70 amounts between the particular layers in both healthy and inflamed pig uteri was demonstrated. Earlier it was reported that NA, ACh, NPY, VIP, GAL and PGE 2 have lowering action on the amplitude in pig inflamed uterus 31,32,38,39,41,43,44 . Thus, it is possible, that CGRP by decreasing the value of this parameter (present study) is another substance which contributes to the accumulation of inflammatory exudate inside the uterine lumen.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the innervation of the inflamed uterus, it is known that in the gilts with endometritis, the numbers of uterine perikarya expressing noradrenaline (NA), neuropeptide Y (NPY) and vasoactive intestinal peptide (VIP) in the CaMG 35 and PCG 36 as well as the sets of uterine perikarya containing substance P (SP) and galanin (GAL) in the DRGs 7 were increased. The participation of NA 31,32,37,38 , acetylcholine (ACh) 39,40 , NPY 41 , somatostatin (SOM) 42 , VIP 43 and GAL 44 in the contractility of inflamed pig uterus in connection with the changes in expression receptors for these transmitters were also reported. It was hypothesized that endometritis affects the myometrial innervation pattern by CGRP nerve fibers and the expression of CLR and CGRP action on the contractile function of an inflamed uterus.…”
mentioning
confidence: 97%
“…In inflamed pig uterus, presence of all α1-and α2-ARs isoforms and all β-ARs subtypes [13], and the lowering effect of NA on its contractility were also revealed [24]. Moreover, the role of particular β-ARs subtypes [16] and particular α2-ARs isoforms [25] in the contractility of pig uterus with inflammation was documented. No data are available on the role of particular α1-ARs isoforms in the contractility of inflamed uterus.…”
Section: Introductionmentioning
confidence: 85%
“…Under physiological conditions, expression of all isoforms of α1-and α2-ARs, and all subtypes of β-ARs, was revealed in myocytes of myometrium (MYO) in animals [5][6][7][8][9][10][11][12][13]. Activation of α-ARs by NA stimulates, while activation of β-ARs decreases, myometrial contractility [14][15][16]. All isoforms of α1-ARs participate in the regulation of rat uterine contractility [5,6,8,17].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the control of inflamed uterus contractility, the importance of metabolites of arachidonic acids, such as prostaglandin (PG)F2α [ 8 ], PGE2 [ 9 ], PGI2 [ 10 ], leukotriene (LT)C4 and LTD4 [ 11 ] in pigs, as well as PGF2α during the postpartum period in cows [ 12 ], have been reported. Studies have also been devoted to the role of noradrenaline (NA) [ 9 , 10 , 13 , 14 , 15 ], acetylcholine (ACh) [ 16 , 17 ], neuropeptide Y (NPY) [ 18 ], somatostatin [ 19 ], vasoactive intestinal peptide (VIP) [ 20 ] and galanin (GAL) [ 21 ] in the contractility of porcine inflamed uterus, together with the function of receptors for these neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%